Association of frailty and its trajectory with the risk of cancer: evidence from the China health and retirement longitudinal study (CHARLS) - Qian Gao; Pengfei Li; Zhengyang Lu; Muye Ma; Nan Zhang; Youhua Lu; Jinming Yu (BMC Public Health)
Abstract Background Frailty can be identified in both middle-aged and older adults. However, longitudinal studies that examine whether frailty is associated with incident cancer are currently lacking. This study aimed to comprehensively examine the impact of baseline frailty levels and their changing trajectories over time on the risk of cancer. Methods We assessed frailty status using the frailty index based on data from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2020. First, the association between baseline frailty and cancer risk was analyzed using the Cox proportional hazards model. Second, based on the CHARLS data from 2011 to 2020, we used Group-based trajectory modeling (GBTM) to identify trajectories of frailty development during the four follow-up periods from 2011 to 2020. Cox proportional hazards model was used to analyze the association between frailty trajectories and the risk of cancer incidence during the follow-up period. Results A total of 17,708 participants were involved at the baseline survey in CHARLS 2011. During a mean follow-up period of 8.05 years, 248 cancer events occurred. Compared with non-frailty individuals, participants in pre-frailty and frailty states had a 34% (hazard ratio [HR]: 1.34, 95% confidence interval [CI]: 1.03–1.75) and 66% (HR: 1.66, 95% CI: 1.07–2.56) increased risk of overall cancer incidence, respectively. Based on repeated measurements from 2011 to 2018, three trajectories of frailty were identified among 9,173 participants. Compared to the low-level stable group, the high-level increase group had the highest risk of cancer, with an associated HR (95% CI) of 5.43 (1.07–5.73). This was followed by the medium-level increase group, with an associated HR (95% CI 2.86 (1.27–6.43). When stratified by sex and age, participants aged ≥ 60 years and female participants in the high-level increase frailty group had a higher risk of developing cancer. Conclusion Frailty is associated with cancer risk. Medium and high levels of the frailty index are significantly associated with an increased risk of cancer incidence. In addition, more attention should be paid to the risk of cancer in people aged ≥ 60 years and in women with high levels of frailty.